Redefinition of territorial limits of a conservation unit in the Brazilian Amazon: the case of the Jamanxim National Forest, state of Pará, Brazil - Pinheiro, Paula Fernanda Viegas; da Silva Júnior, Orleno Marques; Rocha, Gilberto de Miranda; Ruivo, Maria de Lourdes Pinheiro; Maciel, Maria de Nazaré Martins; Braga, Thaís Gleice Martins; Ferreira, Oberdan Oliveira (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2017)
The National Forest of Jamanxim in the municipality of Novo Progresso Pará state, Brazil, was created in 2006 with hectares, and since its creation has been the scene of conflicts among economic interests that have requested a redrawing of the national forest’s boundaries. The purpose of this article is to analyze how these conflicts are occurring and the measures being taken by local agents and the government in the territorial redefinition of the national forest. Analyzes were carried out through the author’s participation in a working group of the Pará state secretary for the environment in which both local agents and technicians of the Chico Mendes Institute for Biodiversity Conservation were heard Satellite image analysis and the ICMBio report were analyzed whereby only three of the mapped areas were to be excluded from the national forest, which was not accepted by the local agents, a triggering factor of provisional measure 756/2016, vetoed by the president of the Republic as contrary to public interests and unconstitutional. Notably, there are intense conflicts and disputes over territory, causing losses to the conservation of biodiversity and decrease of the natural heritage of the Amazon region.